Strategi Jepang Dalam Mereformasi Administrasi : Literature Review - Ramadhani Haryo Seno (Program Studi Administrasi Negara Universitas Serang Raya, 2020)
Focus of this research is to describe administrative reform process in one country, by finding the strategies of administrative reform in transforming and developing administration system in Japan. Descriptive qualitative analysis by study literature and examining secondary data as a data collection method use in this research. The result show that there are three strategies successful of administrative reform: (1) reorganizations; (2) deregulations; and (3) decentralization. The conclusion of this research that are government must used its power to achieve the stated reform goals. The Japanese government has the courage non-populist policies by dissolving state ministries, recruiting civil servants, undertaking privatization, and gradually a bureaucratic culture that tends not to be innovative. Every change in Japan is preceded by an institutional order that is responsible for a particular problem and is ad-hoc (temporary). This shows that how Japan is controlled for certain problems by having targets that must be resolved. Realizing that political support is inevitable and even a necessity in implementing administrative reform in Japan.